Heidi - Spyri, Johanna; Hall, Eileen Leslie, Cecil Ibbotson, Eva (Puffin New York, 2009)
Heidi, a Swiss orphan, is heartbroken when she must leave her home and grandfather to go to school and care for a sick girl named Clara in the city